Purification and Characterization of a New Antifungal Compound 10-(2,2-dimethyl-cyclohexyl)-6,9-dihydroxy-4,9-dimethyl-dec-2-enoic Acid Methyl Ester from Streptomyces hydrogenans Strain DH16 - Kaur, Talwinder; Kaur, Amarjeet; Sharma, Vishal; Manhas, Rajesh K. (Frontiers in Microbiology, 2016)
In agriculture, biocontrol agents have been emerged as safe alternative to chemical pesticides where Streptomyces spp. and their metabolites constitute a great potential for their exploration as potent agents for controlling various fungal phytopathogens. The present study reports an antifungal compound purified from Streptomyces hydrogenans strain DH16, a soil isolate, using silica gel chromatography and semi preparative HPLC. The compound was characterized using various spectroscopic techniques (IR, 1H and 13C NMR) and named 10-(2,2-dimethyl-cyclohexyl)-6,9-dihydroxy-4,9-dimethyl-dec-2-enoic acid methyl ester (SH). Compound (SH) showed significant inhibitory activity against fungal phytopathogens and resulted in severe morphological aberrations in their structure. Minimal inhibitory and minimal fungicidal concentrations of the compound ranged from 6.25 to 25µg/ml and 25 to 50 µg/ml, respectively. In vivo evaluation of the compound showed strong control efficacy against A. brassicicola, a seed borne pathogen, on radish seeds. In comparison to mancozeb and carbendazim, the compound was more effective in controlling damping off disease. Additionally, it promoted plant growth with increased rate of seed germination, and displayed no phytotoxicity. The compound retained its antifungal activity after its exposure to temperature of 100 °C and sunlight for 1 h. Furthermore, the compound (SH) when tested for its biosafety was found to be non-cytotoxic, and non- mutagenic against Salmonella typhimurium TA98 and TA100 strains. This purified compound from S. hydrogenans strain DH16 has not been reported earlier, so this new compound can be developed as an ideal safe and superior biofungicide for the control of various fungal plant diseases.